Relationship Of Compensation With Nurse Performance In Medan Muhammadiyah Hospital Year 2022 - Miftahul Jannah (Science Midwifery, 2022)
Performance is the result of a person's work as well as a benchmark to determine the results or achievements of a person's work or tasks assigned to the employee. An important factor that must be considered to improve performance is compensation. Compensation is very important for nurses because compensation is everything that nurses receive in return for their work. The things that need to be measured from compensation are direct financial compensation, indirect financial compensation and non-financial compensation. This study aims to determine the relationship between compensation and nurse performance. This type of research is an analytical study with a cross sectional approach, a sample of 39 people, the sampling technique is saturated sampling, the measuring scale in this study is the Guttman scale. The analysis used is univariate analysis and bivariate analysis. Data analysis used chi-square test. The results are as follows: direct financial compensation P (0.012) indirect financial compensation P (0.022) and non-financial compensation P (0.001). Each of these variables shows direct evidence of nurse performance, financial compensation directly with performance (p<0.05=0.012) on financial compensation indirectly with performance (p<0.05=0.022) on non-financial compensation with performance (p <0.005 = 0.001) then there is a significant relationship between compensation and the performance of nurses at the Muhammadiyah Medan Hospital in 2022. Compensation is related to the performance of nurses, so it is expected that respondents can improve their performance in hospitals